Effect of non-stoichiometry on the crystal nucleation and growth in oxide glasses. (November 2019) - Fokin, Vladimir M.; Abyzov, Alexander S.; Rodrigues, Alisson M.; Pompermayer, Rogerio Z.; Macena, Guilherme S.; Zanotto, Edgar D.; Ferreira, Eduardo B.
Abstract: Non-stoichiometric glasses (NSG) are much more common than stoichiometric compositions. However, due to inherent difficulties, fundamental studies of crystallization kinetics of NSG are much less frequent. To shed light on the crystal nucleation and growth kinetics of NSG, we adopted a nucleation kinetics model, leaving the interfacial energy and diffusion coefficient as free parameters, to explain experimental nucleation data of glasses of three compositions in the pseudo-binary Li2 O·2SiO2 –BaO·2SiO2 model system. We show that, as the glass composition approaches the eutectic, the nucleation rates drop drastically, mainly due to an increase in the interfacial energy. This result corroborates the common empirical observation that eutectic compositions tend to show good glass-forming ability. We also found that the structural relaxation times are significantly shorter than the characteristic nucleation times, validating the widely used and scarcely tested assumption that relaxation does not play a noticeable role in crystal nucleation. For a stoichiometric glass the fitted diffusion coefficient determining nucleation, D, is lower than that determining the growth of macro crystals, D U, and this difference significantly increases with decreasing temperature. On the other hand, the diffusion coefficient calculated from viscosity, D η, is close to D U at high temperatures and approaches D in the glass transition range. Finally, after crystallization of the primary phase (lithium disilicate), barium disilicate and more lithium disilicate crystals precipitate in the diffusion zone existing in the residual glass. Graphical abstract: Image 1